Pengaruh Aplikasi Mikoriza dan Kompos Tandan Kosong Kelapa Sawit terhadap Pertumbuhan dan Produksi Kedelai Hitam (Glycine max L.) - Siahaan, Jefri Andi; Hutapea, Sumihar (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Black soybeans (Glycine max L.) are one of the important food commodities that have high nutritional value, but their production in Indonesia is still low. This study aims to analyze the effect of the application of Arbuscular Mycorrhizal Fungi (FMA) and oil palm empty bunch compost (TKKS) on the growth and production of black soybean plants. The research was carried out in the experimental field using a factorial Group Random Design (RAK) with two factors, namely TKKS (0, 300, and 600 g/plot) and FMA (0, 10, 20, and 30 g/plant), which were repeated three times, respectively. The parameters observed included plant height, stem diameter, number of leaves, leaf area, number of branches, number of pods, and weight of wet and dry seeds. The results of the analysis showed that the administration of TKKS and FMA separately and interactively had a real effect on almost all growth and outcome parameters. The best treatment combination was obtained in K2F3, namely TKKS compost 600 g/plot and FMA 30 g/plant. This study concludes that the integration between TKKS and FMA organic fertilizers can be an effective and sustainable strategy in increasing the productivity of black soybeans